Hubungan Sedentary Lifestyle denganTekanan Darah pada Mahasiswa Keperawatan di Fakultas Ilmu Kesehatan Universitas Muhammadiyah Manado - Rahmat Hidayat Djalil; Zainar Kasim; Sri Hardini Bawenti (Universitas Muhammadiyah Manado, 2024)
Sedentary lifestyle characterized by lack of physical activity among students, especially in the midst of high academic demands. Nursing students of Universitas Muhammadiyah Manado are vulnerable to this lifestyle, which has the potential to affect cardiovascular health, including increased blood pressure. This study aims to analyze the relationship between sedentary life style and blood pressure in nursing students at Universitas Muhammadiyah Manado. This study used descriptive analytic method with cross-sectional approach. A total of 38 respondents participated in this study. Data was collected through a questionnaire that measured the level of sedentary lifestyle and blood pressure. Spearman Rank correlation test was used to analyze the relationship between sedentary lifestyle and blood pressure. The results of this study showed that more than half of the total respondents were in the low sedentary lifestyle category as many as 20 people with a presentation (52.6%) and most were in the normotensive category as many as 28 people with a presentation (73.7%). The results of the spearman rank correlation test with a p value of 0.000, with a p value smaller than alpha (a) = 0.05. In conclusion, there is a significant relationship between sedentary lifestyle and blood pressure in nursing students at Universitas Muhammadiyah Manado. Suggestions for respondents reduce sedentary lifestyle so that it is important to carry out intervention stoin crease physical activity among nursing students.